Identifying psychological resistances to using logic in cognitive-behavioral therapy for psychosis (CBTp) that limit successful outcomes for patients. Issue 4 (2nd October 2019) - Garrett, Michael; Ahmed, Anthony O.; Athineos, Christina; Cruz, Lisa; Harris, Kelly; Del Pozzo, Jill; Forster, Victoria; Gallego, Juan
ABSTRACT: The small to modest effect sizes of cognitive behavioral therapy for psychosis (CBTp) invite the question, do some treatments not succeed because patients mobilize psychological resistances to treatment that limit outcomes? This paper identifies 10 psychological resistances to CBTp, 7 that undermine the use of logic when examining delusional beliefs, and 3 best considered from a psychodynamic viewpoint. Resistances to progress in CBTp defined in the paper include logic evasion, logic monopolizing, logic blinding, logic partitioning, equivocation, reactive reassertion, feeling-percept fusion, mind-guarding, peripheral preoccupation, and external expectancy. When therapists recognize the operation of these defenses, they may aim to diminish their impact on the treatment. Ways the therapist might address these resistances in psychotherapy are suggested.